1989
DOI: 10.1139/b89-381
|View full text |Cite
|
Sign up to set email alerts
|

The structure and development of the haustorium in Cuscuta australis

Abstract: The structure and development of the haustorium of a parasitic angiosperm Cuscuta australis R. Brown growing on the host plant Trifolium repens L. was studied with light and electron microscopy. The upper haustorium, which lies external to the host organ, initiates endogenously from cortical cells of the middle layers of the parasite stem. The initial cells develop into a group of meristematic cells. As haustorial maturation progresses, the meristematic cells develop into an endophyte primordium that penetrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 11 publications
0
22
1
Order By: Relevance
“…Previous literature interprets the dodder haustorium as a highly modified adventitious root (Truscott, 1958;Kuijt, 1976;Lee and Chai, 1989;Lee, 2007). Ultrastructural analysis of the origin of adventitious roots in cuttings of the distant relative petunia (Petunia hybrida) show their origin from cell divisions within the cambium layer itself (Ahkami et al, 2009) in a manner distinct from the dedifferentiation of cortical parenchyma in dodder.…”
Section: Origin Of Haustoriamentioning
confidence: 99%
“…Previous literature interprets the dodder haustorium as a highly modified adventitious root (Truscott, 1958;Kuijt, 1976;Lee and Chai, 1989;Lee, 2007). Ultrastructural analysis of the origin of adventitious roots in cuttings of the distant relative petunia (Petunia hybrida) show their origin from cell divisions within the cambium layer itself (Ahkami et al, 2009) in a manner distinct from the dedifferentiation of cortical parenchyma in dodder.…”
Section: Origin Of Haustoriamentioning
confidence: 99%
“…The mechanism of attachment and the development of haustoria have been studied in detail from a structural perspective (Kuijt and Toth 1976;Lee and Lee 1989;Dawson et al 1994;Vaughn 2002Vaughn , 2003. Haustoria develop on the inner (concave) side of the stem coils and their part that will remain external to the host is called prehaustorium ("upper haustorium"- Lee and Lee 1989;or "adhesive disk"-Dawson et al 1994).…”
Section: Growth and Developmentmentioning
confidence: 99%
“…Haustoria develop on the inner (concave) side of the stem coils and their part that will remain external to the host is called prehaustorium ("upper haustorium"- Lee and Lee 1989;or "adhesive disk"-Dawson et al 1994). The prehaustorium develops endogenously from a disk-like meristem located within the cortex, close to the vascular bundles (Dawson et al 1994).…”
Section: Growth and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the attachment mechanism(s) of the upper haustoria are not known in detail. Field and laboratory investigations have found that many haustoria fail to make functional attachments (Baird and Riopel, 1983;Lee and Lee, 1989;Lesny, 1991). In several parasites, this contact is undoubtedly promoted by the tight adhesion of the upper haustoria to the host surface, thereby reinforcing the subsequent thrust of the invading endophyte (Riopel and Timko, 1995).…”
mentioning
confidence: 99%